Deindustrialization and Implementation of Industry 4.0 - Case of The Republic of Croatia - Marko Tomljanović; Zoran Grubišić; Sandra Kamenković (Journal of Central Banking Theory and Practice, 2019)
The industrial sector of the Republic of Croatia is subject to deindustrialization, which was globally recognized as early as in the 1960s. Such a situation is a challenge in terms of implementing new sources of economic growth and industrial production, with a particular emphasis on investing in research and development, education and their products. Since 2011, special emphasis has been placed on the need to implement the concept of Industry 4.0. The problem surveyed in this research derives from insufficient readiness of the Republic of Croatia to implement Industry 4.0, mainly resulting from its major orientation towards traditional industrial sectors and a low share of high value added activities, which is particularly visible through the share of high technology products in total exports. However, the Republic of Croatia is characterized by low levels of scientific research and innovative activities, which greatly slows down this process. The aim of the conducted research is to present the theoretical aspects of the process of deindustrialization and Industry 4.0, to make projections of the key indicators of deindustrialization and Industry 4.0 until 2025, and to propose scientifically based measures to be taken in the direction of securing digital transformation of the Croatian industry. The purpose of the conducted research is to analyse trends in the industrial sector in the Republic of Croatia and to determine the current state of the (de)industrialization process and the level of implementation of Industry 4.0. The research has showed that the process of deindustrialization in the Republic of Croatia is characterized by a reduction in the share of employment in the primary sector, by a growing employment in the secondary sector, and by a relative increase in industrial production and labour productivity. However, since 2015 there has been an increase in employment in the secondary sector, which is in contrast to the theoretical concepts of deindustrialization and indicates a new trend in the industrial sector. This situation is a challenge concerning the implementation of Industry 4.0, which requires increased investment in research and development and the improvement of knowledge and the ability of the population and their implementation in the economic sector. By analysing this segment of the Croatian economy, some progress has been made. Also, it has also been found that in some segments it significantly lags behind the EU levels.
Keywords: F00; L6; 330; deindustrialization; education; Industry 4.0; Republic of Croatia; research.